Regular and Chaotic Vibrations of a Nonlinear Rotor-Stator System - Urszula Ferdek (Applied Sciences)
The paper is concerned with the analysis of a six-degree-of-freedom non-linear model which describes the vibrations of a rotor. The model takes into account the impacts between the rotating element and a limiter of motion. Using numerical integration and spectrum analysis, the influence of the excitation frequency, static loads, and the position of the limiter of motion on the type of vibrations of the system was studied. A multiparametric analysis has been performed to determine the areas of influence of two system parameters on the type of excited vibrations. Different types of vibration are further illustrated by plots of time histories, frequency spectra, phase portraits, stroboscopic portraits and bifurcation diagrams. The quality index of the system has also been determined and defined as the average value of the rotor kinetic energy. Depending on the parameters of the system, periodic, quasi-periodic or chaotic oscillations take place. The article primarily focuses on the risk of chaotic vibrations occurring in the system.